The constitutionality of the Disaster Management Act and the Covid-19 regulations enacted thereunder: does this regulatory regime contravene the right to just administrative action? - Nchodu, Dimakatso (Department of Public Law, 2023)
his paper covers the constitutionality of the Disaster Management Act known as the Covid19 regulations. It will argue that to keep in line with an open and transparent government in a participatory democracy, we needed a more open and public regulation making process which was less truncated. It argues that had all communities been consulted in the making and enforcing of lockdown regulations there would have been more adherence and less lives lost. Furthermore, because Covid-19 regulation-making is administrative action, had more procedural fairness and participation been included in the process then the right would not have been breached. I will then show that the process was irrational, unreasonable and unlawful, and that the executive used the DMA declaration to exercise powers of emergency and that the lockdown declaration was more a de facto state of emergency and not a state of disaster. I will then set out the socio-economic consequences of the lockdown on gender-based violence, women and children, and early childhood development learners, and how more public participation and giving effect to just admin action could have mitigated these effects. Furthermore, this not only makes this irrational and unconstitutional but also takes us back to Apartheid like powers being exercised by the executive.